Dinamika Temperature Ekstrem di Kepulauan Bangka Belitung Periode 1981-2022 - Utami, Amanda Kurnia; Ariska, Melly; Akhsan, Hamdi; Andriani, Nely (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2024)
This research was carried out to find out the dynamics of climate change in the Bangka Belitung Islands, by utilizing BMKG observer station data at Depati Meteorological Station, starting in 1981 until 2022 that the official obtained from the BMKG website online. This research was conducted at the Education laboratory of FKIP Physics University of Sriwijaya. The research method used is secondary data research with a quantitative approach. Data analysis was used using the RClimDex application with the Expert Team on Climate Change Detection and Indices (ETCCDI) rules. Trend analysis was carried out with non-pithelmetry statistical tests Man-Kendall and Sens tests. The temperature indexes experience significant trends, which indicates that the longer the temperature in the Bangka Belitung Islands will increase.